Roles of the Intramolecular Disulfide Bridge in MotX and MotY, the Specific Proteins for Sodium-Driven Motors in Vibrio spp. - Yagasaki, Jin (American Society for Microbiology, 2006)
The proteins PomA, PomB, MotX, and MotY are essential for the motor function of Na(+)-driven flagella in Vibrio spp. Both MotY and MotX have the two cysteine residues (one of which is in a conserved tetrapeptide [CQLV]) that are inferred to form an intramolecular disulfide bond. The cysteine mutants of MotY prevented the formation of an intramolecular disulfide bond, which is presumably important for protein stability. Disruption of the disulfide bridge in MotX by site-directed mutagenesis resulted in increased instability, which did not, however, affect the motility of the cells. These lines of evidence suggest that the intramolecular disulfide bonds are involved in the stability of both proteins, but only MotY requires the intramolecular bridge for proper function.